Changes in the nutritive value and aerobic stability of corn silages inoculated with Bacillus subtilis alone or combined with Lactobacillus plantarum - Lara, Erika C. [UNESP]; Basso, Fernanda C. [UNESP]; Assis, Flavia B. de [UNESP]; Souza, Fernando A. [UNESP]; Berchielli, Telma T. [UNESP]; Reis, Ricardo A. [UNESP] (Csiro Publishing, 2016)
Chemical composition, fermentation characteristics, in vitro digestibility and aerobic stability were evaluated in corn silage inoculated with microbial additives in two different experiments. Inoculant treatments (untreated, Bacillus subtilis and B. subtilis combined with Lactobacillus plantarum) were applied to fresh forages. Chopped corn plants (2B655 Hx) were ensiled in laboratory silos for periods of 7, 14, 21 and 63 days to evaluate the fermentation parameters. The experimental silos were weighed to determine gas losses. After the ensiling period, the silage was sampled to determine chemical composition and in vitro organic matter digestibility. To evaluate aerobic stability, chopped corn plants (AG-1051) were ensiled in laboratory silos that were opened after 96 days of ensiling. The silage was placed in different buckets containing data loggers. The silage was sampled after 0, 4, 8 and 12 days of exposure to air to evaluate the microbial populations and pH. The data were analysed as a completely randomised design using a mixed repeated-measures model in the MIXED procedure of SAS. To evaluate each treatment relative to the fermentation times, a regression analysis using the PROC REG procedure of SAS was applied. A significance level of P < 0.05 was used. Inoculation with both strains increased lactic acid concentration, whereas the use of B. subtilis alone or combined with L. plantarum improved in vitro apparent organic matter digestibility. In the B. subtilis and B. subtilis combined with L. plantarum silages, moulds and yeasts decreased, and aerobic stability was improved. Inoculation with B. subtilis alone or combined with L. plantarum improved the nutritional value and aerobic stability of corn silage.
Keywords: aerobic deterioration; bacterial inoculant; chemical composition; lactic acid bacteria